2011
DOI: 10.19030/ijmis.v16i1.6723
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Social Media Tools For Sell vs Buy Activities Into Emerging And Developed Markets

Abstract: This paper studies usage patterns of global sellers and buyers using five forms of Web 2.0 social broadcast behaviors -blogging, micro-blogging, social networking, online video, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The term social media is a broad concept that encompasses a number of applications, which vary widely in scope and function. They include a whole variety of different social networking sites, such as Facebook, micro-blogging services like Twitter, blogs, photo sharing and video sharing like YouTube or Flickr (Gilfoil, 2012). All of them, however, contain several common features that are potentially useful for engaging with the public, in the form of user-generated content and real-time communication.…”
Section: Social Mediamentioning
confidence: 99%
“…The term social media is a broad concept that encompasses a number of applications, which vary widely in scope and function. They include a whole variety of different social networking sites, such as Facebook, micro-blogging services like Twitter, blogs, photo sharing and video sharing like YouTube or Flickr (Gilfoil, 2012). All of them, however, contain several common features that are potentially useful for engaging with the public, in the form of user-generated content and real-time communication.…”
Section: Social Mediamentioning
confidence: 99%
“…This argument appears to have validity as computers and telephones, in certain societies, put people who own or use them in an elite category (Olaniran, 2007). At the same time, social media usage in emerging markets is still in the early stages of the adoption process (Gilfoil, 2012). Hence social media as a chosen communication channel may present organizations with the challenge of how to capture older demographics who may lack access or do not use social media.…”
Section: Practical Challenges and Opportunitiesmentioning
confidence: 99%
“…The use of social media as a marketing tool in emerging markets or any markets for that matter may make economic sense (Gilfoil, 2012;Parveen et al, 2015). To this end, many scholars have suggested that Web 2.0 can add to the power of viral marketing (Hartline et al, 2008;Leskovec et al, 2007;Subramani and Rajagopalan, 2003).…”
Section: Practical Challenges and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible exceptions to this statement include a study that addresses the potential benefit to emerging economies of employing Internet based marketing in the area of eco-tourism through company websites and blogs (Sambhanthan & Good, 2012). Also, some researchers have studied social media and microblog traffic relating to buying and selling activities and compare data for developed versus emerging markets (Gilfoil, 2012;Jobs, 2011;Jobs & Gilfoil, 2011). These studies, however, do not examine SMM activity of actual companies and limit their observations of emerging economies to the BRIC group (Brazil, Russia, India, China) and NIC (Mexico, Malaysia) markets.…”
Section: Review Of the Literaturementioning
confidence: 99%